Determinants of Behavioral Finance Influencing Investment Decisions with Respect to Income: A Study on Investment in the Equity Market - Rekha. D.M. (International Journal of Advanced Science and Technology, 2020)
Investment in the Indian equity market with the participation of not more than 7% ofthe population is comparatively slowly developed due to various reasons, one being the lack of understanding of the behavioral biases and its impact on investment decision. The present paper aims to explore the behavioural determinants influencing individual investors’ decisions in the Indian equity market. Moreover, the level of influence of these factors on investment decisions is also investigated. Further, the differences in the investment decisions and behavioral determinants on the basis of respondents’ income level have also been analysed. The hypotheses of the study are tested through questionnaires and the responses obtained from 550 investors in Bangalore were evaluated. The collected data analysed using SPSS 24. The result shows that herding, heuristics, prospect and market determinants are four most significant behavioural finance paradigms affecting the investment decisions of individual investors in the Indian equity market. Most of the variables from all factors have significant impacts whereas availability bias from heuristic factor has no significant influence on investment decision. Among the different behavioural factors, representativeness from heuristic factors, mental accounting from prospect factors, past trends and recommendation from market and herding factors indicates a highly significant positive impact on investment decision. Overall, the prospect factors represent the most important factor having the highest significant impact on investment decision making followed by market factors.Keywords: Behavioral finance, behavioural determinants, equity market, investment decision, income level